PENDIDIKAN SEKS BAGI ANAK BERKEBUTUHAN KHUSUS - Safrudin Aziz (Jurnal Kependidikan, 2014)
Nowadays, sex education for children with special needs becomes a necessity. In term of it, besides based on philosophical and juridical, sex education is the preventive efforts in order that every child with special needs can recognize, understand, handle his/her biological development and change. In addition sex education for children with special needs also aims at guiding them to appreciate other peopleâ€™s sexual behavior and not to make them being stuck on deviate sex conduct as well as not getting violence and sexual abuse from others. This is because their physical and psychological condition, which has some problems, enables them to be easily manipulated and courted, so that many of them are often stuck to be the object of sexual harassment of irresponsible person. This writing specifically is going to explain the concept of sex education for children with special needs, which includes characteristic of children with special needs, theory of sex education, the anvil of sex education, as well as material, method, and teacher competencies in the implementation of sex education for them.Â Pendidikan seks bagi anak berkebutuhan khusus kini menjadi sebuah keniscayaan. Perihal tersebut selain didasarkan secara filosofis maupun yuridis, pendidikan seks merupakan upaya preventif agar setiap anak berkebutuhan khusus dapat mengenali, memahami dan mengelola perkembangan dan perubahan secara biologis pada dirinya, menghargai perilaku seks orang lain, serta tidak terjebak pada perilaku seks yang menyimpang ataupun mendapatkan kekerasan dan pelecehan seks dari orang lain. Sebab seiring dengan kondisi fisik dan psikologi yang bermasalah menjadikan anak berkebutuhan khusus mudah dimanipulasi, dirayu, sehingga kerap kali terjebak untuk dijadikan objek pelampiasan syahwat oleh orang yang berkepribadian buruk. Tulisan ini secara khusus akan menguraikan tentang konsep pendidikan seks bagi anak berkebutuhan khusus mencakup karakteristik anak berkebutuhan khusus, teori pendidikan seks, landasan pendidikan seks, materi, metode serta kompetensi guru dalam pelaksanaan pendidikan seks.